Pertanggung Jawaban Hukum terhadap Penjual yang Melakukan Wanprestasi dalam Jual Beli Online - Ismi Lailatul Maulida; Ahmad Heru Romadhon (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Contemporary digital advancements have significantly impacted the manner in which individuals engage in economic activities, as evidenced by the rising volume of online transactions. While offering convenience and efficiency, electronic transactions also provide numerous legal challenges, especially regarding seller defaults, including delayed delivery, goods that do not conform to the agreement, or sellers failing to meet their duties post-payment by consumers. This scenario may result in consumer losses, necessitating sufficient legal certainty and protection. This study seeks to analyze the legal regulations pertaining to contracts and defaults in digital platform transactions and to evaluate the types of legal liabilities that may be placed on sellers. This study employs normative legal research, focusing on legislative and conceptual approaches, and utilizes primary, secondary, and tertiary legal materials as data references. The study's findings reveal that seller liability regulations in electronic transactions are defined in the Civil Code, the Consumer Protection Law, and the Law on Electronic Information and Transactions. Nonetheless, its execution has several challenges, especially concerning evidence and the efficacy of law enforcement measures. Consequently, it is imperative to enhance the function of marketplaces and establish more adaptive legislative frameworks to guarantee consumer protection and restitution for losses in online commerce.